Using historical maps in scientific studies : applications, challenges, and best practices /: applications, challenges, and best practices. ([2020]) - Chiang, Yao-Yi; Duan, Weiwei; Leyk, Stefan; Uhl, Johannes H; Knoblock, Craig A, 1962-
No abstract available